Respuesta :
2x-x-7=0
3x-7=0
add 7 to 7 and 0, so then we cross out 7-7, and then
3x=7, bc u change the subtraction to addition, sr if thst doesn't make sense but 3x=7 is the answer
3x-7=0
add 7 to 7 and 0, so then we cross out 7-7, and then
3x=7, bc u change the subtraction to addition, sr if thst doesn't make sense but 3x=7 is the answer
x^2 - x - 7 = 0
x^2 - x = 7
x^2 - x + 0.25 = 7 + 0.25
(x - 0.5)^2 = 7.25
x - 0.5 = (+ - ) sqrt 7.25
x = 0.5 (+-) 2.69
x = 0.5 + 2.69 = 3.19 <==
x = 0.5 - 2.69 = -2.19 <==
x^2 - x = 7
x^2 - x + 0.25 = 7 + 0.25
(x - 0.5)^2 = 7.25
x - 0.5 = (+ - ) sqrt 7.25
x = 0.5 (+-) 2.69
x = 0.5 + 2.69 = 3.19 <==
x = 0.5 - 2.69 = -2.19 <==